Role of community participation in wildlife conservation (Zoological Records and Reviews, 2024)
Community participation in wildlife conservation -- encompassing citizen science monitoring, co-managed protectedareas, community-based natural resource management, and stakeholder engagement in conservation planning -- isincreasingly recognised as essential for achieving durable biodiversity outcomes at landscape scales. This studyevaluates the conservation effectiveness and social legitimacy of community participation approaches across 42 wildlifeconservation initiatives in Denmark, the Netherlands, and Spain using a mixed-methods framework combiningbiodiversity outcome data (n = 14,284 species records), governance quality assessments (IUCN good governancecriteria), and structured social surveys (n = 2,184 participants). Initiatives with high community participation scores (CPS>= 7/10) showed significantly better wildlife biodiversity outcomes than those with low participation (CPS < 4/10) acrossall three countries (mean inside-initiative species richness ratio 1.48 +- 0.18 vs. 1.12 +- 0.14 relative to outside; t(40) =6.84, p < 0.001). Citizen science programmes contributed 38.4% of total species occurrence records in high-participationinitiatives, with record quality comparable to professional surveys (Cohen's kappa = 0.84 +- 0.06 for identificationaccuracy). Social surveys confirmed that perceived fairness of benefit-sharing was the strongest predictor of long-termparticipation willingness (beta = 0.58 +- 0.09, p < 0.001), exceeding direct economic incentives (beta = 0.34 +- 0.09) andecological awareness (beta = 0.28). Initiatives combining citizen science, co-governance, and direct community benefitshowed the highest combined biodiversity and social outcomes. These findings provide an evidence base for designingcommunity participation frameworks under the Kunming-Montreal GBF Target 22 (inclusive conservation governance)and EU Nature Restoration Law community engagement obligations.